The contents of high-energy phosphates in different fibre types in skeletal muscles from rat, guinea-pig and man. - Edström, L (1982)
1. The contents of high-energy phosphates at rest have been measured in skeletal muscles with different fibre-type composition from rat, guinea-pig and man. All muscles studied biochemically have been characterized histochemically. 2. Fast-twitch muscles had a higher ATP/ADP ratio than slow-twitch muscles and, with the exception of the tongue in the rat, higher contents of ATP and phosphocreatine. 3. There was an inverse relationship between the content of phosphocreatine and the stainability for succinyl dehydrogenase, which is a marker enzyme for oxidative capacity. 4. The biochemical and histochemical data are discussed in relation to known morphological and functional properties of the different muscle-fibre types. It is concluded that fast-twitch fibres have a high ATP/ADP ratio favouring a fast acceleration of energy production. The content of phosphocreatine seems to be related to the glycolytic capacity but not to the contraction time. In addition to being an immediate energy source, phosphocreatine functions as a buffer against lactic acidosis.